2023
DOI: 10.1097/cej.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a nomogram prediction model for axillary lymph node metastasis of cT1 invasive breast cancer

Shuqi Wang,
Dongmo Wang,
Xin Wen
et al.

Abstract: Objective Based on the ultrasonic characteristics of the breast mass and axillary lymph nodes as well as the clinicopathological information, a model was developed for predicting axillary lymph node metastasis in cT1 breast cancer, and relevant features associated with axillary lymph node metastasis were identified. Methods Our retrospective study included 808 patients with cT1 invasive breast cancer treated at the Second Affiliated Hospital and the Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several studies confirmed that cortical thickness is an important predictor of ALN metastasis [29,30].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies confirmed that cortical thickness is an important predictor of ALN metastasis [29,30].…”
Section: Discussionmentioning
confidence: 92%